The great tit abdominal stripe contains a sexually dichromatic colour patch hidden from the human eye - Laczi, Miklós; Herczeg, Gábor; Szabó, Gyula; Gyarmathy, Helga; Sarkadi, Fanni; Török, János; Hegyi, Gergely (Frontiers in Ecology and Evolution, 2023)
Information on the exact nature of sexual dichromatism might be incomplete, often leading to the treatment of dichromatic species as monochromatic. This error is evident when the two sexes of a species look identical to the human eye, as in the great tit (Parus major). We measured reflectance in three sections (throat, breast, belly) of the abdominal black stripe of great tits during the pairing and nestling feeding periods and assessed differences between patch sections, sexes, and seasons using visual models. We found that the stripe, which had previously been considered a single, contiguous patch, consists of multiple patches. In males, the breast section differed markedly from the throat and belly sections in having higher total brightness and ultraviolet chroma, while the female's breast seemed to be less bright than the two other regions, resulting in strong sexual dichromatism hidden from the human eye. Colouration was more pronounced in winter, but dichromatism was present in both periods. The hidden breast ultraviolet patch we discovered in males may act as a sexual ornament or a signal amplifier.